PO115 Patient support program for rrms patients treated with dmf. (1st December 2017) - Berry, Roger; Curlis, Janette; Gribben, Leontia
Abstract : Introduction: In the UK, the number of multiple sclerosis (MS) patients far exceeds the capacity of MS specialist nurses (MSSNs). Methods: Biogen and Quintiles developed a remote, nurse-led, script-based telephone line providing educational assistance and support and promoting treatment adherence among relapsing-remitting MS (RRMS) patients receiving delayed-release dimethyl fumarate (DMF; TECFIDERA). Following DMF initiation, 8 calls are scheduled over the first 3 months, followed by quarterly calls for the remainder of the first treatment year. Results: Based on summarised call data from March 2015-November 2016, 716 patients in the program were referred from 92 of 119 UK prescribing centres, with a mean (median, range) of 7.7 (2, 1–134) patients/centre and averaging 9 calls/patient. Mean call time across all 11 scheduled calls was 72 min (time/call, 5–12 min). Over the 21 months since the program's start (ie, March 2015), cumulative discontinuation among enrolled patients was 13.6%. Of the 56 patients completing satisfaction surveys, 98% reported satisfaction with overall program support; average ranking (scale of 1 [poor] to 5 [excellent]) was 4.9. Discussion: This support program has been widely used and positively received across the UK by DMF-treated patients and aims to reduce burden on MSSNs and promote treatment adherence. Support: Biogen.